Pengelolaan Arsip Di Sekolah Tinggi Ilmu Hukum Sumpah Pemuda Palembang - Vivi Indriani (UIN Sumatera Utara, 2018)
This article discusses about how the condition of archives at Palembang Youth Planning Law School and how the process of managing the archives. This study aims to determine the condition of archives and archive management process. The research method using quantitative is by conducting intensive interviews. The results show that the condition of the archive today can not be said perfect because there are still many that do not fit with as it should. The management of archives at Palembang Youth Planning Law School can be said is not good enough, it can be seen from the management, storage, maintenance and depreciation of the archive that has not been maximized in the implementation. And human resources are still lacking and the background of the head of management is not an archivist but in the field of law